Determinants of finance and taxation affecting sustainable Economic Expansion and Public welfare amidst structural shifts - S. V. Karpova; V. S. Kudryashov (Economics, taxes & law, 2026)
The significance of this research lies in its focus on the necessity of grasping financial and tax mechanisms from both theoretical and practical standpoints. In contemporary times, these mechanisms play a crucial role in shaping investment, regional differences, the financial sector’s performance, and the country’s socioeconomic stability. The study’s subject focuses on the financial, tax, investment, and regional elements that drive long-term economic expansion and affect living standards. The research aims to identify and organize the key factors influencing sustainable socioeconomic development. It also attempts to evaluate the institutional and macroeconomic environments that shape current economic growth mechanisms. This study’s methodology basis integrates systems and institutional perspectives, employing economic and statistical analysis, correlation and regression techniques, and a synthesis of findings from Russian and international empirical research. Using these tools, the authors could assess from multiple angles the influence of financial development, tax policy, investment, sanctions, and regional elements on the economy. The scientific novelty lies in the thorough analysis across different levels of financial and tax factors influencing sustainable growth, integrating macroeconomic, sectoral, regional, and behavioral elements. The authors’ findings are that integrating financial, tax, sanctions, and social considerations into a unified analytical model enabled a more complete understanding of the forces that shape quality of life amidst structural transformations. This research’s practical value lies in its conclusions as potential to inform tax and budget policy improvements, shape regional development initiatives, create investment support mechanisms, and guide strategies for enhancing public financial literacy.